Influence of seasonal and edaphic factors on the diversity of scolopendromorph centipedes (Chilopoda: Scolopendromorpha) and general observations on their ecology from Kerala, India - Dhanya Balan; P. M. Sureshan (Journal of Threatened Taxa, 2017)
Scolopendromorph centipedes (Chilopoda: Scolopendromorpha) are a diverse group of invertebrate communities, which play significant, but often poorly acknowledged or understood roles in the delivery of soil ecosystem services.  In the present paper we analyze the impact of seasonal and edaphic factors on the species diversity of scolopendromorph centipedes based on the field studies conducted in three selected sites.  The study sites included a protected forest ecosystem, an undisturbed isolated hillock and a residential plot at Kozhikode District, Kerala, India.  The study was performed from April 2011 to November 2012.  Overall 486 individuals belonging to 18 species under the families Cryptopidae and Scolopendridae were collected.  The range of Shannon-Wiener diversity was 0.89–2.58 and Simpson diversity was 1.91–13.69.  Species diversity is also influenced by variations in seasons and various physico–chemical properties of soil in the study area. General observations on parental care, moulting, hibernation and ectoparasitism were also included.